Determinants Of K6 Antenatal Care Visits Among Third Trimester Pregnant Women At Pahandut Health Center In Palangka Raya City - Cindy Fastika; Riny Natalina; Sukmawaty A Damiti; Sery Wahyuni (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
The coverage rate of K6 Visits for pregnant women at the Pahandut Health Center in Palangkaraya City of 86.72% has not yet met the target of 100%. There are several factors that influence pregnant women in making ANC visits, namely behavioral factors and factors outside of behavior. The purpose of this study was to determine the Determinants of Antenatal Care K6 Visits for pregnant women at the Pahandut Health Center in Palangka Raya City. This study used an Observational Analytical research design with a cross-sectional approach to identify the Determinants of Antenatal Care K6 visits at the Pahandut Health Center. The instrument in this study was a questionnaire and this study used Univariate and Bivariate data analysis. Bivariate analysis showed a significant relationship between Knowledge (ρ = 0.007), Attitude (ρ = 0.017), Husband's Support (ρ = 0.035), Distance of Residence (ρ = 0.040) with K6 coverage. While the relationship is not significant between Job (ρ = 0.445) with K6 coverage. Based on the results of the study, it was found that there was a significant relationship between Knowledge, Attitude, Husband's Support and Distance of Residence with K6 ANC Visits, while there was no relationship between Job and K6 ANC Visits.